5(x-4)+2(x+1)=3(2-4)

Simple and best practice solution for 5(x-4)+2(x+1)=3(2-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-4)+2(x+1)=3(2-4) equation:


Simplifying
5(x + -4) + 2(x + 1) = 3(2 + -4)

Reorder the terms:
5(-4 + x) + 2(x + 1) = 3(2 + -4)
(-4 * 5 + x * 5) + 2(x + 1) = 3(2 + -4)
(-20 + 5x) + 2(x + 1) = 3(2 + -4)

Reorder the terms:
-20 + 5x + 2(1 + x) = 3(2 + -4)
-20 + 5x + (1 * 2 + x * 2) = 3(2 + -4)
-20 + 5x + (2 + 2x) = 3(2 + -4)

Reorder the terms:
-20 + 2 + 5x + 2x = 3(2 + -4)

Combine like terms: -20 + 2 = -18
-18 + 5x + 2x = 3(2 + -4)

Combine like terms: 5x + 2x = 7x
-18 + 7x = 3(2 + -4)

Combine like terms: 2 + -4 = -2
-18 + 7x = 3(-2)

Multiply 3 * -2
-18 + 7x = -6

Solving
-18 + 7x = -6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 7x = -6 + 18

Combine like terms: -18 + 18 = 0
0 + 7x = -6 + 18
7x = -6 + 18

Combine like terms: -6 + 18 = 12
7x = 12

Divide each side by '7'.
x = 1.714285714

Simplifying
x = 1.714285714

See similar equations:

| 14-2q-5=-2q+9 | | -8v-4v= | | -3*-5=51 | | 8g-2g= | | p=45-q | | 9q+(-4q)= | | 92=4+6w+2w | | 7w+4w= | | 8p+(-6p)+6m= | | 6r+5t+4r= | | 8e+3(5+e)=10 | | 6x+8(2x+3)= | | 2x+3+3x+2=180 | | 5(x-6)+8=7x-10 | | 185-5x=31x+21 | | 2k+5=12 | | 0=(-(x+4)(x+4))-7 | | 40+14y=-20-8y-6 | | 7z+4=-5z-2 | | -12=3(2n-10) | | 5y-3x+2y-4x= | | 4x-6=-31 | | -3y+2x= | | 7x+-12=2 | | 30x-25=50-20x | | -8d-(-2d)-6d= | | 16-x+2=23 | | 15b-24b= | | 888x=111 | | 7t+4t= | | N=zx-d | | 6rs+5r+8s-rs-r-s= |

Equations solver categories